Coastal Resource-Based Entrepreneurship: A Strategy to Improve the Quality of Life of Coastal Area Communities - Yulia Novita; Andika Isma (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2023)
This research is a descriptive qualitative research using observation, interview and documentation data collection. The research subject is the community of Untia Fishermen Village in Makassar City, totaling 5 informants who have various incomes ranging from agriculture, fisheries and marine potential in Untia Fishermen Village. The results showed that coastal communities need knowledge and understanding of entrepreneurship and how to process coastal resources. The process of community empowerment through coastal resource-based entrepreneurship training in accordance with the empowerment stage, namely the stages of training implementation, namely planning, counseling, coastal resource-based entrepreneurship training activities, mentoring and evaluation. Supporting factors such as the positive response of the community, adequate natural potential as the main raw material and support from the government, while the inhibiting factors for empowerment through manufacturing training are lack of capital, packaging equipment is still rarely sold, and the community has not been able to optimize the training process and has not been able to manage time. Hopefully, coastal resource-based entrepreneurship is an emerging concept as a potential solution for wise management of coastal natural resources with the aim of maintaining the sustainability of natural resources and the environment, while increasing the income and quality of life of coastal communities.